O imaginário do corpo poético no trânsito das linguagens - Bruni, Rosana Artiaga Cunha (2018)
The present research puts in perspective the realization of a practical theoretical study about the Imaginary and some key notions in this investigation as imagination, intuition and synchronicity. Using as a research methodology the Matrix Analysis Method applied to the auto-ethnographic investigations of creative processes in dance-theater, elaborates the understanding of the image as an imaginary device, recognizes the reverie as a method of creation in the Scenic Arts, being the transliteration of languages one of its possible practical effects.